Development Strategy for Disadvantaged Village Communities in Lembang District - Abd Rasyid; Mustamin; Tri bambang Prasetio (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2023)
Disadvantaged villages are villages that have minimal availability and access to basic services, infrastructure, accessibility of public services, and governance. Pinrang Regency is known as one of the national food buffer agricultural areas. But on the other hand, Pinrang Regency still has several areas or villages that are still very underdeveloped. Of course this condition seems to be a contradiction between the regions known as rice granaries, on the other hand there are social and infrastructural problems in several mountain villages, especially in Lembang District. The purpose of this research is to analyze and examine the social problems of underdeveloped rural communities and find strategies in implementing village community development, especially villages that have been designated as very underdeveloped villages by the Ministry of Villages in 2022, especially in Lembang District, Pinrang Regency, including Lembang Village. The method used in this research is qualitative, namely a research method that uses a naturalistic approach to seek and find understanding or meaning of phenomena in a specific context. This approach is intended to see and describe the social conditions of society. Thus, to analyze the development strategy of underdeveloped rural communities in Lembang District, this research began with mapping through Focus Group Discussions (FGD) to explore the potential of village communities and the problems they faced as well as conducting interviews and forming a Working Group (Pokja) as a strategic step.